Analisis Dampak Nonton Pornografi terhadap Keharmonisan Keluarga dan Remaja Perspektif Maqashid Syariah - Uliamri; Mufti Kamal (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The development of digital technology has increased access to pornographic content, impacting family life and adolescent morality. Exposure to pornography not only affects individual behavior but also potentially weakens family harmony, parenting quality, and the internalization of moral values among the younger generation. This study aims to analyze the impact of pornography on family harmony and adolescent moral development from the perspective of Maqashid al-Shariah. Using a qualitative approach with library research, data were collected from books, scientific articles, regulations, and official reports, then analyzed using content analysis and thematic analysis. The findings indicate that pornography exposure correlates with decreased marital satisfaction, weakened communication and commitment between partners, and increased family conflict. Among adolescents, pornography contributes to distorted sexual understanding, reduced self-control, increased permissive attitudes toward risky sexual behavior, and weakened moral values. From the Maqashid al-Shariah perspective, these conditions contradict the objectives of Islamic law in preserving religion (ḥifẓ al-dīn), intellect (ḥifẓ al-'aql), life (ḥifẓ al-nafs), and lineage (ḥifẓ al-nasl). This study offers a conceptual contribution by integrating the analysis of pornography's impact on family harmony and adolescent moral development within the Maqashid al-Shariah framework, serving as a foundation for strengthening family resilience, moral education, and digital literacy in the modern era.